Evaluation of the intraocular scattering through brightness reduction by glare using external diffusers to simulate cataracts - Barrionuevo, Pablo; Colombo, Elisa; Corregidor, Diego; Jaen, Mirta; Issolio, Luis (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
In this work, we evaluate the feasibility to determine the intraocular scattering by measuring the brightness reduction by glare. A haploscopic system based on the brightness comparison has been developed. This system allows to compare the brightness of a test with a steady glare source in the field of vision, and another one without it. Our goal is to study the sensibility of the proposed methodology to quantify the intraocular scattering. In this first approach, we use physically and psychophysically characterized external diffusers to simulate different degrees of cataracts. The results have been shown in terms of the glare index. This index increases as the level of filter scattering rises, and even more when the diffuser is set up on only one eye. Besides, the system allows to discriminate among slightly different levels of scattering. The repeatability of the results and the resistance to fraud of the methodology have been analyzed.
Optica Applicata, Vol. 40, 2010, nr 1, s. 63-75
Keywords: optyka; brightness; glare; intraocular scattering